Assessment of wireless power transfer technology for emergency power response - Awal, M. R. (Institute of Electrical and Electronics Engineers Inc., 2016)
The impact of the natural disaster is devastating. Wireless power transfer technology is very promising to reduce this impact by providing power backup for communication devices. This paper presents the assessment of the wireless power transfer technologies for long distance energy transfer. The review of several wireless power transfer technologies (WPTT), namely inductive, capacitive, acoustic, and optical, are presented. The WPTTs are evaluated in the context of several criteria, specifically, propagation area, power level, and efficiency. From the evaluation, it is evident that, optical WPTT is highly suitable for long distance power transfer. It can cover a large area with considerable power. Moreover, it can be merged with the PV technology on the receiving end, which proves its superiority over other technologies in the context of application compatibility.